How to train in relational mediation in the language class? Analysis from the perspective of the Common European Framework of Reference for Languages. Companion Volume with New Descriptors - Sujecka-Zając, Jolanta (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
We propose to analyze the contribution of the three major works produced by the experts of the Council of Europe and to contribute to a better understanding of the concept of mediation and, in particular, of relational mediation in the language class. Our objective is to follow the terminological and conceptual evolution of the term to arrive at a pedagogical profile of relational mediation that we could then set up in the classroom to ensure genuine language teaching. This analysis stems from the interest attributed to the relational factor following the current COVID-19 pandemic, which has clearly shown the great importance of these questions for educational success.